Comparison of Neurodegeneration and Cognitive Impairment in Neonatal Mice Exposed to Propofol or Isoflurane - Yang, Bin (Public Library of Science, 2014)
BACKGROUND: While previous studies have demonstrated neuronal apoptosis and associated cognitive impairment after isoflurane or propofol exposure in neonatal rodents, the effects of these two anesthetics have not been directly compared. Here, we compare and contrast the effectiveness of isoflurane and propofol to cause neurodegeneration in the developing brain and associated cognitive dysfunction. METHODS: Seven-day-old mice were used. Mice in the isoflurane treatment group received 6 h of 1.5% isoflurane, while mice in propofol treatment group received one peritoneal injection (150 mg/kg), which produced persistent anesthesia with loss of righting for at least 6 h. Mice in control groups received carrying gas or a peritoneal injection of vehicle (intralipid). At 6 h after anesthetic treatment, a subset of each group was sacrificed and examined for evidence of neurodegeneration, using plasma levels of S100β, and apoptosis using caspase-3 immunohistochemistry in the cerebral cortex and hippocampus and Western blot assays of the cortex. In addition, biomarkers for inflammation (interleukin-1, interleukin-6, and tumor necrosis factor alpha) were examined with Western blot analyses of the cortex. In another subset of mice, learning and memory were assessed 32 days after the anesthetic exposures using the Morris water maze. RESULTS: Isoflurane significantly increased plasma S100β levels compared to controls and propofol. Both isoflurane and propofol significantly increased caspase-3 levels in the cortex and hippocampus, though isoflurane was significantly more potent than propofol. However, there were no significant differences in the inflammatory biomarkers in the cortex or in subsequent learning and memory between the experimental groups. CONCLUSION: Both isoflurane and propofol caused significant apoptosis in the mouse developing brain, with isoflurane being more potent. Isoflurane significantly increased levels of the plasma neurodegenerative biomarker, S100β. However, these neurodegenerative effects of isoflurane and propofol in the developing brain were not associated with effects on inflammation or with cognitive dysfunction in later life.